A novel long non-coding RNA XLOC_004787, is associated with migration and promotes cancer cell proliferation by downregulating mir-203a-3p in gastric cancer - Renjie Miao; Zhendong Yao; Bingheng Hu; Tao Jin; Donglai Zhu; Yun Shi; Yuhua Gong; Shihe Shao; Chen Shao (BMC Gastroenterology, 2023)
Abstract Background Long noncoding RNAs (lncRNAs) have been identified as important regulatory factors implicated in a wide array of diseases, including various forms of cancer. However, the roles of most lncRNAs in the progression of gastric cancer (GC) remain largely unexplored. This study investigates the biological function and underlying mechanism of a novel lncRNA, XLOC_004787 in GC. Methods The location of XLOC_004787 in GES-1 cells and HGC-27 cells were detected by fluorescence in situ hybridization (FISH) assay. The expression levels of XLOC_004787 were assessed using quantitative real-time fluorescence PCR (qRT-PCR) in various cell lines, including GES-1, MGC-803, MKN-45, BGC-823, SGC-7901, and HGC-27 cells. Functional assays such as Transwell migration, cell counting kit-8 (CCK-8), and colony formation experiments were employed to analyze the effects of XLOC_004787 and miR-203a-3p on cell migration and proliferation. Protein levels associated with GC in these cell lines were examined by Western blotting. The intracellular localization of β-catenin and P-Smad2/3 was assessed using immunofluorescence (IF) assay. Additionally, the interaction between XLOC_004787 and miR-203a-3p was investigated using a dual luciferase assay. Results XLOC_004787 was localized at both the cytoplasm and nucleus of GES-1 cells and HGC-27 cells. Compared to normal tissues and GES-1 cells, XLOC_004787 expression was significantly upregulated in GC tissues and cells, with the highest and lowest expression observed in SGC-7901 and HGC-27 cells, respectively. Furthermore, a reduced expression of XLOC_004787 was seen to inhibit migration and proliferation in SGC-7901 cells. Western blotting analysis revealed that a decrease in XLOC_004787 expression correspondingly decreased the expression of N-cadherin, mmp2, mmp9, Snail, Vimentin, β-catenin, C-myc, Cyclin D1, and TGF-β, while concurrently increasing E-cadherin expression. This was also associated with diminished expression of P-Smad2/3 in relation to Smad2/3, and reduced P-Gsk3β expression in comparison to Gsk3β. Additionally, the nuclear entry of P-Smad2/3 and β-catenin was reduced by lower XLOC_004787 expression. Amplifying XLOC_004787 expression via pcDNA_XLOC_004787 suggested a potential for cancer promotion. Notably, XLOC_004787 was found to negatively regulate mir-203a-3p expression, with potential binding sites identified between the two. Higher mir-203a-3p expression was observed to decrease migration and proliferation, and enhance E-cadherin expression. Conversely, suppression of mir-203a-3p expression suggested a potential promotion of proliferation and migration in GC cells. Conclusions These results suggest that XLOC_004787, found to be upregulated in GC tissues, potentially promotes proliferation and migration in GC cells. This occurs through the activation of TGF-β and Wnt/β-catenin signaling pathways and the expression of EMT-related proteins. Additionally, XLOC_004787 may influence cell migration and proliferation by modulating the signaling pathway via the adsorption and inhibition of mir-203a-3p.